162k views
5 votes
Let f(x) = 3x2 + x − 3 and g(x) = x2 − 5x + 1. Find f(x) − g(x). (1 point)

2x2 − 4x − 2

2x2 − 4x − 4

2x2 + 6x − 2

2x2 + 6x − 4

User Prithis
by
5.9k points

2 Answers

1 vote

Answer:

2x^2 + 6x - 4.

Explanation:

This is 3x^2+ x - 3 - (x^2 - 5x + 1) (Note we put the last function in brackets).

Distributing the negative over the brackets:

3x^2 + x - 3 - x^2 + 5x - 1

= 2x^2 + 6x - 4 (answer).

User Vallentin
by
4.6k points
3 votes

Answer: The correct option is

(D)
f(x)-g(x)=2x^2+6x-4.

Step-by-step explanation: We are given the following two functions :


f(x)=3x^2+x-3,\\\\g(x)=x^2-5x+1.

We are to find the expression for f(x) - g(x).

We have


f(x)-g(x)\\\\=(3x^2+x-3)-(x^2-5x+1)\\\\=3x^2+x-3-x^2+5x-1\\\\=2x^2+6x-4.

Thus,
f(x)-g(x)=2x^2+6x-4.

Option (D) is CORRECT.

User Kgibbon
by
4.9k points